Moral Agency Conditions: Moral Agent, Limited Moral Agent, Quasi-Moral Agent - S. V. Glebova; N. V. Perova (Дискурс)
Introduction. The concept  of “moral agent” and its boundaries  are  not  currently  clearly defined.  Given the  connection between  moral  agency  and moral  responsibility,  it seems necessary to introduce  a clear  definition of “moral agent”, as  well as  to differentiate  the types of moral agency. The hypothesis  of this article is that although the notion of a moral agent in itself is rather limited, there  are a number of “borderline” groups, the definition of the status of which needs to be clarified.Methodology and sources. The article  provides an ethical  and philosophical  analysis of approaches to the definition of a moral agency, a comparative  analysis of the concepts of a moral agent and a moral subject,  as well as approaches to determining the moral statuses of  various  “borderline”  groups  in the  context  of  the  works  of  J.  MacMurray, A.  Taylor, I. Kant, M Rowlands, J. Searle and others.Results and discussion. The article  presents an  analysis  of  the  definitions  of a “moral agent”, highlights the key features  that make it possible  to speak of a moral agency as an independent  moral  concept,  as  well as  determine  the  conditions  for the  onset  of moral agency.  To differentiate  the  types  of moral  agents,  the  article  introduces  the  concept  of “limited moral agent” to denote  the special status of children and the mentally ill. Evidence is provided that  people  belonging  to  these  categories may have  the  status  of  a  moral agent, although not to the extent  that this status  initially implies. As part of the definition of artificial intelligence as a “quasi-moral agent”, the key features  of AI in the framework of moral communication  between  AI and a person are identified.Conclusion.  Based  on the  analysis, the  article proposes a number  of requirements for a moral  agency.  Based  on these  requirements, it is proposed  to  distinguish such  types  of moral agency as a limited moral agent, including children and the mentally ill, as well as a quasi-moral agent, which is an artificially created  agent, including artificial intelligence.